Promotions and Themes: An Empirical Analysis of Attendance Factors in the National Women's Soccer League - Lena Gunn; Alexander Traugutt (Journal of Applied Sports Management, 2025)
The National Women's Soccer League (NWSL) has experienced significant growth, making it crucial to understand attendance drivers at matches. This study evaluated the impact of themed events and promotions on attendance during the 2023 NWSL season. Using data from all regular-season home matches (N = 167), an OLS regression analyzed how various factors influenced attendance measured as a percentage of stadium capacity. Results revealed that themed events significantly increased attendance, while traditional promotions showed a positive but non-significant effect. External factors including post-World Cup timing, visiting team marquee players, and market demographics also significantly influenced attendance. These findings provide actionable insights for NWSL teams seeking to optimize marketing strategies and enhance match attendance.
Keywords: Marketing; Attendance; Women' s Soccer